Motivational Factors that Facilitate Student-Athlete Academic Achievement - Kane, Thomas D.; Dale, Logan R. (My University, 2006)
Contemporary theories of academic and work motivation offer alternative techniques for effectively advising student-athletes. Understanding which motivating factors most strongly relate to academic achievement provides athletic/academic advisors with meaningful information for constructively assisting the performance of their advisees. This study tested the degree to which the content of academic goals, self-efficacy, and goal-orientation predicted the academic achievement of 220 student-athletes. Results indicated that motivation variables predicted student semester academic achievement above and beyond what was predicted by student ACT score and high school class rank. Also, the motivation variables as a group were as strongly related to academic achievement as ACT and class rank. Among all variables studied, the difficulty of the student's semester goal most strongly contribution to student achievement. Results encouraged optimism among academic advisors who wish to integrate goal-setting techniques into advisement protocols. Discussion focused on strategies to help student-athletes set quality academic goals. Motivational variables predicted student-athlete success in the classroom above and beyond traditional admissions criteria such as high school class rank and ACT score. Among motivational variables, the difficulty of the student's semester goals, as rated by academic advisors, turned out to most strongly influence semester GPA.
Keywords: skills; academic performance; academic predictors